APLICAÇÃO DA ESPECTROSCOPIA (LIBS) NA ANÁLISE DE CONTAMINANTES EM ESCAMA DE PEIXES - Thiemy da Costa Shimada, Julia; de Oliveira Souza, Bianca; Humberto da Cunha Andrade, Luis; Marcio Lima, Sandro; Eduardo Lima Junior, Sidnei (ANAIS DO ENIC, 2026)
-